Reconsidering Gobitis: An Exercise in Presidential Leadership - Robert L. Tsai (Washington University Law Review, 2008)
In June of 1940, the Supreme Court ruled 8-1 in Minersville School District v. Gobitis that the First Amendment posed no barrier to the punishment of two school-age Jehovah's Witnesses who refused to pay homage to the American flag. Three years later, the Justices reversed themselves in West Virginia State Board of Education v. Barnette. This sudden change has prompted a host of explanations. Some observers have stressed changes in judicial personnel in the intervening years; others have pointed to the wax and wane of general anxieties over the war; still others have emphasized the sympathy-inspiring acts of terror visited upon Jehovah's Witnesses in the wake of Gobitis. Drawing upon previously unearthed archival material, this article for the first time attributes a major role to presidential initiative. A sophisticated strategy implemented by the Roosevelt administration systematically eroded the picture of political life constructed by Gobitis, presented an alternative reading of the First Amendment in urgent fashion, and rhetorically empowered advocates for the pro-rights position. Despite what many believed to be a deliberative moment, however, the Supreme Court incompletely memorialized the interaction between the branches of government. In copying the President's words without attribution and purging the record of executive branch participation, the Barnette Court impoverished our appreciation of the constitutional system in action. Understanding the remarkable debate over the right of conscience within this paradigm sheds light on a variety of enduring questions, from the strategies, utilized by presidents to control political pathways, to the origins of the First Amendment's centrality to the modern order.
Keywords: First Amendment protections (United States Constitution); Leadership; Executive power; Minersville School District v. Gobitis